Entre bandeiras, altares e santos: a Folia de Reis de Itaguari na perspectiva do patrimônio cultural - Cabral, Igor Junqueira (2020)
Folia de Reis involves heritage, identity, signs, rituals, elements that make up popular Catholicism. Devotional acts linked to the sacredness of saints who have not even been canonized. This research, inscribed in the line of research identity, territoriality and tradition, contemplates the field of materiality in the Folias de Reis Itaguarinas seeking to understand how the Folia acted resisting the modernities that mark the 21st century. In this context, it is appropriate to approach that it consists of a universalization process that hierarchizes the erudite culture and the popular culture. I carried out an analysis of this materiality in view of the changes that this religious manifestation has undergone over the years, its modernization due to the growth of the party, the incorporation of new values and signs and the protagonism of the female gender. I take as a problem the need to understand tradition as cultural resistance, to observe the Folias de Reis Itaguarinas as it behaves about the materiality of sacred objects. The procedures adopted involve field research with survey of sources based on the subjects' orality, participant and ethnographic observation, aiming at an analysis of the dense description of the data. The results show that the need to compose a field of identity that leads the subjects to resignify their traditions and this process directly affects materiality as an element of power, meaning and construction of their own culture